What Goes in Must Come Out? The Metabolic Profile of Plants and Caterpillars, Frass, And Adults of Asota (Erebidae: Aganainae) Feeding on Ficus (Moraceae) in New Guinea - Fontanilla, Alyssa M; Aubona, Gibson; Sisol, Mentap; Kuukkanen, Ilari; Salminen, Juha-Pekka; Miller, Scott E; Holloway, Jeremy D; Novotny, Vojtech; Volf, Martin; Segar, Simon T (Journal of chemical ecology, 2022)
Insect herbivores have evolved a broad spectrum of adaptations in response to the diversity of chemical defences employed by plants. Here we focus on two species of New Guinean Asota and determine how these specialist moths deal with the leaf alkaloids of their fig (Ficus) hosts. As each focal Asota species is restricted to one of three chemically distinct species of Ficus, we also test whether these specialized interactions lead to similar alkaloid profiles in both Asota species. We reared Asota caterpillars on their respective Ficus hosts in natural conditions and analyzed the alkaloid profiles of leaf, frass, caterpillar, and adult moth samples using UHPLC-MS/MS analyses. We identified 43 alkaloids in our samples. Leaf alkaloids showed various fates. Some were excreted in frass or found in caterpillars and adult moths. We also found two apparently novel indole alkaloids-likely synthesized de novo by the moths or their microbiota-in both caterpillar and adult tissue but not in leaves or frass. Overall, alkaloids unique or largely restricted to insect tissue were shared across moth species despite feeding on different hosts. This indicates that a limited number of plant compounds have a direct ecological function that is conserved among the studied species. Our results provide evidence for the importance of phytochemistry and metabolic strategies in the formation of plant-insect interactions and food webs in general. Furthermore, we provide a new potential example of insects acquiring chemicals for their benefit in an ecologically relevant insect genus.
Keywords: Biodiversity; Plants; Insecta; Host-specificity; Herbivory; Food-webs; můry; Alkaloids; tandemová hmotnostní spektrometrie; rostliny; Nová Guinea; býložravci; larva; Animals; Ficus; hmyz; Plant–insect interactions; zvířata; Metabolome; Herbivores; Larva; metabolom; New Guinea; Tandem Mass Spectrometry; alkaloidy; Moths